SARS-CoV-2 induces human plasmacytoid predendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (J Exp Med, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here we have isolated primary SARS-CoV-2 viral strains and studied their interaction with human plasmacytoid predendritic cells (pDCs), a key player in antiviral immunity. We show that pDCs are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.
Keywords: Biomarkers; Cell Plasticity; COVID-19; Cytokines; Dendritic Cells; Host-Pathogen Interactions; Humans; Hydroxychloroquine; Immunomodulation; Immunophenotyping; Inflammation Mediators; Interferon Type I; Interferons; Interleukin-1 Receptor-Associated Kinases; Membrane Transport Proteins; SARS-CoV-2

SARS-CoV-2 induces human plasmacytoid pre-dendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (bioRxiv, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here, we have isolated primary SARS-CoV-2 viral strains, and studied their interaction with human plasmacytoid pre-dendritic cells (pDC), a key player in antiviral immunity. We show that pDC are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.

SARS-CoV-2-related MIS-C: A key to the viral and genetic causes of Kawasaki disease? - Sancho-Shimizu, Vanessa; Brodin, Petter; Cobat, Aurelie; Biggs, Catherine M; Toubiana, Julie; Lucas, Carrie L; Henrickson, Sarah E; Belot, Alexandre; Tangye, Stuart G; Milner, Joshua D; Levin, Michael; Abel, Laurent; et al. (J Exp Med, 2021)
Multisystem inflammatory syndrome in children (MIS-C) emerged in April 2020 in communities with high COVID-19 rates. This new condition is heterogenous but resembles Kawasaki disease (KD), a well-known but poorly understood and clinically heterogenous pediatric inflammatory condition for which weak associations have been found with a myriad of viral illnesses. Epidemiological data clearly indicate that SARS-CoV-2 is the trigger for MIS-C, which typically occurs about 1 mo after infection. These findings support the hypothesis of viral triggers for the various forms of classic KD. We further suggest that rare inborn errors of immunity (IEIs) altering the immune response to SARS-CoV-2 may underlie the pathogenesis of MIS-C in some children. The discovery of monogenic IEIs underlying MIS-C would shed light on its pathogenesis, paving the way for a new genetic approach to classic KD, revisited as a heterogeneous collection of IEIs to viruses.
Keywords: Biomarkers; Child; COVID-19; Cytokines; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammation; Inflammation Mediators; Lymphohistiocytosis, Hemophagocytic; Models, Biological; Mucocutaneous Lymph Node Syndrome; Pandemics; SARS-CoV-2; Systemic Inflammatory Response Syndrome

SPEN haploinsufficiency causes a neurodevelopmental disorder overlapping proximal 1p36 deletion syndrome with an episignature of X chromosomes in females. - Radio, Francesca Clementina; Pang, Kaifang; Ciolfi, Andrea; Levy, Michael A; Hernandez-Garcia, Andres; Pedace, Lucia; Pantaleoni, Francesca; Liu, Zhandong; de Boer, Elke; Jackson, Adam; Bruselles, Alessandro; McConkey, Haley; et al. (Am J Hum Genet, 2021)
Deletion 1p36 (del1p36) syndrome is the most common human disorder resulting from a terminal autosomal deletion. This condition is molecularly and clinically heterogeneous. Deletions involving two non-overlapping regions, known as the distal (telomeric) and proximal (centromeric) critical regions, are sufficient to cause the majority of the recurrent clinical features, although with different facial features and dysmorphisms. SPEN encodes a transcriptional repressor commonly deleted in proximal del1p36 syndrome and is located centromeric to the proximal 1p36 critical region. Here, we used clinical data from 34 individuals with truncating variants in SPEN to define a neurodevelopmental disorder presenting with features that overlap considerably with those of proximal del1p36 syndrome. The clinical profile of this disease includes developmental delay/intellectual disability, autism spectrum disorder, anxiety, aggressive behavior, attention deficit disorder, hypotonia, brain and spine anomalies, congenital heart defects, high/narrow palate, facial dysmorphisms, and obesity/increased BMI, especially in females. SPEN also emerges as a relevant gene for del1p36 syndrome by co-expression analyses. Finally, we show that haploinsufficiency of SPEN is associated with a distinctive DNA methylation episignature of the X chromosome in affected females, providing further evidence of a specific contribution of the protein to the epigenetic control of this chromosome, and a paradigm of an X chromosome-specific episignature that classifies syndromic traits. We conclude that SPEN is required for multiple developmental processes and SPEN haploinsufficiency is a major contributor to a disorder associated with deletions centromeric to the previously established 1p36 critical regions.
Keywords: Adolescent; Autism Spectrum Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosome Disorders; Chromosomes, Human, Pair 1; Chromosomes, Human, X; DNA Methylation; DNA-Binding Proteins; Epigenesis, Genetic; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; RNA-Binding Proteins; Young Adult

SVEP1 is a human coronary artery disease locus that promotes atherosclerosis. - Jung, In-Hyuk; Elenbaas, Jared S; Alisio, Arturo; Santana, Katherine; Young, Erica P; Kang, Chul Joo; Kachroo, Puja; Lavine, Kory J; Razani, Babak; Mecham, Robert P; Stitziel, Nathan O (Sci Transl Med, 2021)
A low-frequency variant of sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SVEP1), an extracellular matrix protein, is associated with risk of coronary disease in humans independent of plasma lipids. Despite a robust statistical association, if and how SVEP1 might contribute to atherosclerosis remained unclear. Here, using Mendelian randomization and complementary mouse models, we provide evidence that SVEP1 promotes atherosclerosis in humans and mice and is expressed by vascular smooth muscle cells (VSMCs) within the atherosclerotic plaque. VSMCs also interact with SVEP1, causing proliferation and dysregulation of key differentiation pathways, including integrin and Notch signaling. Fibroblast growth factor receptor transcription increases in VSMCs interacting with SVEP1 and is further increased by the coronary disease-associated variant p.D2702G. These effects ultimately drive inflammation and promote atherosclerosis. Together, our results suggest that VSMC-derived SVEP1 is a proatherogenic factor and support the concept that pharmacological inhibition of SVEP1 should protect against atherosclerosis in humans.

Sequential targeted exome sequencing of 1001 patients affected by unexplained limb-girdle weakness. - Topf, Ana; Johnson, Katherine; Bates, Adam; Phillips, Lauren; Chao, Katherine R; England, Eleina M; Laricchia, Kristen M; Mullen, Thomas; Valkanas, Elise; Xu, Liwen; Bertoli, Marta; Blain, Alison; et al. (Genet Med, 2020)
PURPOSE: Several hundred genetic muscle diseases have been described, all of which are rare. Their clinical and genetic heterogeneity means that a genetic diagnosis is challenging. We established an international consortium, MYO-SEQ, to aid the work-ups of muscle disease patients and to better understand disease etiology. METHODS: Exome sequencing was applied to 1001 undiagnosed patients recruited from more than 40 neuromuscular disease referral centers; standardized phenotypic information was collected for each patient. Exomes were examined for variants in 429 genes associated with muscle conditions. RESULTS: We identified suspected pathogenic variants in 52% of patients across 87 genes. We detected 401 novel variants, 116 of which were recurrent. Variants in CAPN3, DYSF, ANO5, DMD, RYR1, TTN, COL6A2, and SGCA collectively accounted for over half of the solved cases; while variants in newer disease genes, such as BVES and POGLUT1, were also found. The remaining well-characterized unsolved patients (48%) need further investigation. CONCLUSION: Using our unique infrastructure, we developed a pathway to expedite muscle disease diagnoses. Our data suggest that exome sequencing should be used for pathogenic variant detection in patients with suspected genetic muscle diseases, focusing first on the most common disease genes described here, and subsequently in rarer and newly characterized disease genes.
Keywords: Anoctamins; Exome; Glucosyltransferases; Humans; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic Americans; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Severe neurodevelopmental disease caused by a homozygous TLK2 variant. - Topf, Ana; Oktay, Yavuz; Balaraju, Sunitha; Yilmaz, Elmasnur; Sonmezler, Ece; Yis, Uluc; Laurie, Steven; Thompson, Rachel; Roos, Andreas; MacArthur, Daniel G; Yaramis, Ahmet; Güngör, Serdal; et al. (Eur J Hum Genet, 2020)
A distinct neurodevelopmental phenotype characterised mainly by mild motor and language delay and facial dysmorphism, caused by heterozygous de novo or dominant variants in the TLK2 gene has recently been described. All cases reported carried either truncating variants located throughout the gene, or missense changes principally located at the C-terminal end of the protein mostly resulting in haploinsufficiency of TLK2. Through whole exome sequencing, we identified a homozygous missense variant in TLK2 in a patient showing more severe symptoms than those previously described, including cerebellar vermis hypoplasia and West syndrome. Both parents are heterozygous for the variant and clinically unaffected highlighting that recessive variants in TLK2 can also be disease causing and may act through a different pathomechanism.
Keywords: Adult; Cerebellum; Child; Developmental Disabilities; Female; Heterozygote; Homozygote; Humans; Infant; Male; Mutation, Missense; Nervous System Malformations; Pedigree; Protein Kinases; Spasms, Infantile

Short stature and growth hormone deficiency in a subset of patients with Potocki-Lupski syndrome: Expanding the phenotype of PTLS. - Franciskovich, Rachel; Soler-Alfonso, Claudia; Neira-Fresneda, Juanita; Lupski, James R; McCann-Crosby, Bonnie; Potocki, Lorraine (Am J Med Genet A, 2020)
Potocki-Lupski Syndrome (PTLS, MIM 610883), or duplication of chromosome 17p11.2, is a clinically recognizable condition characterized by infantile hypotonia, failure to thrive, developmental delay, intellectual disability, and congenital anomalies. Short stature, classified as greater than two standard deviations below the mean, has not previously been considered a major feature of PTLS. Retrospective chart review on a cohort of 37 individuals with PTLS was performed to investigate the etiology of short stature. Relevant data included anthropometric measurements, insulin growth factor-1 (IGF-1), insulin-like growth factor binding protein 3 (IGFBP-3), growth hormone (GH) stimulation testing, blood glucose levels, brain MRI, and bone age. Approximately 25% (9/37) of individuals with PTLS had short stature. Growth hormone deficiency (GHD) was definitively identified in two individuals. These two PTLS patients with growth hormone deficiency, as well as three others with short stature and no documented GHD, received growth hormone and obtained improvement in linear growth. One individual was identified to have pituitary abnormalities on MRI and had complications of hypoglycemia due to unrecognized GHD. Individuals with PTLS can benefit from undergoing evaluation for GHD should they present with short stature or hypoglycemia. Early identification of GHD could facilitate potential therapeutic benefit for individuals with PTLS, including linear growth, musculoskeletal, and in cases of hypoglycemia, potentially cognitive development as well.

Spectrum of genetic variants in moderate to severe sporadic hearing loss in Pakistan. - Ramzan, Memoona; Bashir, Rasheeda; Salman, Midhat; Mujtaba, Ghulam; Sobreira, Nara; Witmer, P Dane; Naz, Sadaf (Sci Rep, 2020)
Hearing loss affects 380 million people worldwide due to environmental or genetic causes. Determining the cause of deafness in individuals without previous family history of hearing loss is challenging and has been relatively unexplored in Pakistan. We investigated the spectrum of genetic variants in hearing loss in a cohort of singleton affected individuals born to consanguineous parents. Twenty-one individuals with moderate to severe hearing loss were recruited. We performed whole-exome sequencing on DNA samples from the participants, which identified seventeen variants in ten known deafness genes and one novel candidate gene. All identified variants were homozygous except for two. Eleven of the variants were novel, including one multi-exonic homozygous deletion in OTOA. A missense variant in ESRRB was implicated for recessively inherited moderate to severe hearing loss. Two individuals were heterozygous for variants in MYO7A and CHD7, respectively, consistent with de novo variants or dominant inheritance with incomplete penetrance as the reason for their hearing loss. Our results indicate that similar to familial cases of deafness, variants in a large number of genes are responsible for moderate to severe hearing loss in sporadic individuals born to consanguineous couples.
Keywords: Adolescent; Amino Acid Sequence; Audiometry, Pure-Tone; Child; Child, Preschool; Deafness; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Hearing Loss; Heterozygote; Homozygote; Humans; Mutation, Missense; Pakistan; Phenotype; Whole Exome Sequencing; Young Adult

Spinal muscular atrophy diagnosis and carrier screening from genome sequencing data. - Chen, Xiao; Sanchis-Juan, Alba; French, Courtney E; Connell, Andrew J; Delon, Isabelle; Kingsbury, Zoya; Chawla, Aditi; Halpern, Aaron L; Taft, Ryan J; Bentley, David R; Butchbach, Matthew E R; Raymond, F Lucy; et al. (Genet Med, 2020)
PURPOSE: Spinal muscular atrophy (SMA), caused by loss of the SMN1 gene, is a leading cause of early childhood death. Due to the near identical sequences of SMN1 and SMN2, analysis of this region is challenging. Population-wide SMA screening to quantify the SMN1 copy number (CN) is recommended by the American College of Medical Genetics and Genomics. METHODS: We developed a method that accurately identifies the CN of SMN1 and SMN2 using genome sequencing (GS) data by analyzing read depth and eight informative reference genome differences between SMN1/2. RESULTS: We characterized SMN1/2 in 12,747 genomes, identified 1568 samples with SMN1 gains or losses and 6615 samples with SMN2 gains or losses, and calculated a pan-ethnic carrier frequency of 2%, consistent with previous studies. Additionally, 99.8% of our SMN1 and 99.7% of SMN2 CN calls agreed with orthogonal methods, with a recall of 100% for SMA and 97.8% for carriers, and a precision of 100% for both SMA and carriers. CONCLUSION: This SMN copy-number caller can be used to identify both carrier and affected status of SMA, enabling SMA testing to be offered as a comprehensive test in neonatal care and an accurate carrier screening tool in GS sequencing projects.
Keywords: Base Sequence; Child; Child, Preschool; Humans; Muscular Atrophy, Spinal; Survival of Motor Neuron 1 Protein

Spondyloepimetaphyseal dysplasia with elevated plasma lysosomal enzymes caused by homozygous variant in MBTPS1. - Carvalho, Daniel R; Speck-Martins, Carlos E; Brum, Jaime M; Ferreira, Carlos R; Sobreira, Nara L M (Am J Med Genet A, 2020)
Variants in MBTPS1 (membrane-bound transcription factor peptidase, site 1) encoding the protein convertase site-1 protease (S1P) were recently reported in a single individual with skeletal dysplasia and elevated plasma lysosomal enzymes. Here, we report the second individual with this newly described autosomal recessive spondyloepiphyseal dysplasia (OMIM #618392), presenting severe growth retardation, cataract and dysmorphic features, mainly retromicrognathia. Epilepsy and craniosynostosis were novel findings in our proband. She was found to be homozygous for a novel nonsense variant p.Trp983Ter in MBTPS1. In addition, she had normal levels of lysosomal enzyme activity in leukocytes but elevated levels in plasma. Our description confirms the existence of this new skeletal dysplasia and expands the phenotype and genotype of the disease.
Keywords: Cataract; Child, Preschool; Female; Humans; Lysosomal Storage Diseases; Lysosomes; Pedigree; Phenotype; Proprotein Convertases; Serine Endopeptidases

A structural variation reference for medical and population genetics. - Collins, Ryan L; Brand, Harrison; Karczewski, Konrad J; Zhao, Xuefang; Alföldi, Jessica; Francioli, Laurent C; Khera, Amit V; Lowther, Chelsea; Gauthier, Laura D; Wang, Harold; Watts, Nicholas A; Solomonson, Matthew; et al. (Nature, 2020)
Structural variants (SVs) rearrange large segments of DNA and can have profound consequences in evolution and human disease. As national biobanks, disease-association studies, and clinical genetic testing have grown increasingly reliant on genome sequencing, population references such as the Genome Aggregation Database (gnomAD) have become integral in the interpretation of single-nucleotide variants (SNVs). However, there are no reference maps of SVs from high-coverage genome sequencing comparable to those for SNVs. Here we present a reference of sequence-resolved SVs constructed from 14,891 genomes across diverse global populations (54% non-European) in gnomAD. We discovered a rich and complex landscape of 433,371 SVs, from which we estimate that SVs are responsible for 25-29% of all rare protein-truncating events per genome. We found strong correlations between natural selection against damaging SNVs and rare SVs that disrupt or duplicate protein-coding sequence, which suggests that genes that are highly intolerant to loss-of-function are also sensitive to increased dosage. We also uncovered modest selection against noncoding SVs in cis-regulatory elements, although selection against protein-truncating SVs was stronger than all noncoding effects. Finally, we identified very large (over one megabase), rare SVs in 3.9% of samples, and estimate that 0.13% of individuals may carry an SV that meets the existing criteria for clinically important incidental findings. This SV resource is freely distributed via the gnomAD browser and will have broad utility in population genetics, disease-association studies, and diagnostic screening.
Keywords: Continental Population Groups; Disease; Female; Genetic Testing; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genotyping Techniques; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Reference Standards; Selection, Genetic; Whole Genome Sequencing

Successful treatment of intractable epilepsy with ketogenic diet therapy in twins with ALG3-CDG. - Paketci, C; Edem, P; Hiz, S; Sonmezler, E; Soydemir, D; Sarikaya Uzan, G; Oktay, Y; O'Heir, E; Beltran, S; Laurie, S; Töpf, A; Lochmuller, H; et al. (Brain Dev, 2020)
BACKGROUND: Congenital disorders of glycosylation (CDG) is a heterogeneous group of congenital metabolic diseases with multisystem clinical involvement. ALG3-CDG is a very rare subtype with only 24 cases reported so far. CASE: Here, we report two siblings with dysmorphic features, growth retardation, microcephaly, intractable epilepsy, and hemangioma in the frontal, occipital and lumbosacral regions. RESULTS: We studied two siblings by whole exome sequencing. A pathogenic variant in ALG3 (NM_005787.6: c.165C > T; p.Gly55=) that had been previously associated with congenital glycolysis defect type 1d was identified. Their intractable seizures were controlled by ketogenic diet. CONCLUSION: Although prominent findings of growth retardation and microcephaly seen in our patients have been extensively reported before, presence of hemangioma is a novel finding that may be used as an indication for ALG3-CDG diagnosis. Our patients are the first reported cases whose intractable seizures were controlled with ketogenic diet. This report adds ketogenic diet as an option for treatment of intractable epilepsy in ALG3-CDG.
Keywords: Central Nervous System Neoplasms; Congenital Disorders of Glycosylation; Craniofacial Abnormalities; Developmental Disabilities; Diet, Ketogenic; Drug Resistant Epilepsy; Female; Hemangioma; Humans; Infant; Male; Mannosyltransferases; Twins; Whole Exome Sequencing

Systems Analysis Implicates WAVE2 Complex in the Pathogenesis of Developmental Left-Sided Obstructive Heart Defects. - Edwards, Jonathan J; Rouillard, Andrew D; Fernandez, Nicolas F; Wang, Zichen; Lachmann, Alexander; Shankaran, Sunita S; Bisgrove, Brent W; Demarest, Bradley; Turan, Nahid; Srivastava, Deepak; Bernstein, Daniel; Deanfield, John; et al. (JACC Basic Transl Sci, 2020)
Genetic variants are the primary driver of congenital heart disease (CHD) pathogenesis. However, our ability to identify causative variants is limited. To identify causal CHD genes that are associated with specific molecular functions, the study used prior knowledge to filter de novo variants from 2,881 probands with sporadic severe CHD. This approach enabled the authors to identify an association between left ventricular outflow tract obstruction lesions and genes associated with the WAVE2 complex and regulation of small GTPase-mediated signal transduction. Using CRISPR zebrafish knockdowns, the study confirmed that WAVE2 complex proteins , , and and the regulators of small GTPase signaling and are critical to cardiac development.

SMAD4 rare variants in individuals and families with thoracic aortic aneurysms and dissections. - Duan, Xue-Yan; Guo, Dong-Chuan; Regalado, Ellen S; Shen, Hong; Coselli, Joseph S; Estrera, Anthony L; Safi, Hazim J; Bamshad, Michael J; Nickerson, Deborah A; LeMaire, Scott A; De Backer, Julie; Milewicz, Dianna M (Eur J Hum Genet, 2019)
SMAD4 pathogenic variants cause juvenile polyposis (JPS) and hereditary hemorrhagic telangiectasia (HHT), and 40% of affected individuals also have thoracic aortic disease. At the same time, SMAD4 pathogenic variants have not been reported in thoracic aortic disease families without JPS-HHT. A SMAD4 heterozygous variant, c.290G>T, p.(Arg97Leu), not present in population databases and predicted to be damaging to protein function, was identified in a family with thoracic aortic disease and no evidence of HHT or JPS. Cellular studies revealed that the SMAD4 p.(Arg97Leu) alteration increased SMAD4 ubiquitination and 26S proteasome-mediated protein degradation. Smooth muscle cells (SMCs) infected with lentivirus expressing the SMAD4 p.(Arg97Leu) variant demonstrated reduced contractile protein gene expression when compared to that of wild-type SMAD4. In addition, two rare variants were identified in individuals with early age of onset of thoracic aortic dissection. These results suggest that SMAD4 rare missense variants can lead to thoracic aortic disease in individuals who do not have JPS or HHT.

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures. - Zweier, Markus; Begemann, Anaïs; McWalter, Kirsty; Cho, Megan T; Abela, Lucia; Banka, Siddharth; Behring, Bettina; Berger, Andrea; Brown, Chester W; Carneiro, Maryline; Chen, Jiani; Cooper, Gregory M; et al. (Eur J Hum Genet, 2019)
CYFIP2, encoding the evolutionary highly conserved cytoplasmic FMRP interacting protein 2, has previously been proposed as a candidate gene for intellectual disability and autism because of its important role linking FMRP-dependent transcription regulation and actin polymerization via the WAVE regulatory complex (WRC). Recently, de novo variants affecting the amino acid p.Arg87 of CYFIP2 were reported in four individuals with epileptic encephalopathy. We here report 12 independent patients harboring a variety of de novo variants in CYFIP2 broadening the molecular and clinical spectrum of a novel CYFIP2-related neurodevelopmental disorder. Using trio whole-exome or -genome sequencing, we identified 12 independent patients carrying a total of eight distinct de novo variants in CYFIP2 with a shared phenotype of intellectual disability, seizures, and muscular hypotonia. We detected seven different missense variants, of which two occurred recurrently (p.(Arg87Cys) and p.(Ile664Met)), and a splice donor variant in the last intron for which we showed exon skipping in the transcript. The latter is expected to escape nonsense-mediated mRNA decay resulting in a truncated protein. Despite the large spacing in the primary structure, the variants spatially cluster in the tertiary structure and are all predicted to weaken the interaction with WAVE1 or NCKAP1 of the actin polymerization regulating WRC-complex. Preliminary genotype-phenotype correlation indicates a profound phenotype in p.Arg87 substitutions and a more variable phenotype in other alterations. This study evidenced a variety of de novo variants in CYFIP2 as a novel cause of mostly severe intellectual disability with seizures and muscular hypotonia.

Severe neurocognitive and growth disorders due to variation in THOC2, an essential component of nuclear mRNA export machinery. - Kumar, Raman; Gardner, Alison; Homan, Claire C; Douglas, Evelyn; Mefford, Heather; Wieczorek, Dagmar; Lüdecke, Hermann-Josef; Stark, Zornitza; Sadedin, Simon; Nowak, Catherine Bearce; Douglas, Jessica; Parsons, Gretchen; et al. (Hum Mutat, 2018)
Highly conserved TREX-mediated mRNA export is emerging as a key pathway in neuronal development and differentiation. TREX subunit variants cause neurodevelopmental disorders (NDDs) by interfering with mRNA export from the cell nucleus to the cytoplasm. Previously we implicated four missense variants in the X-linked THOC2 gene in intellectual disability (ID). We now report an additional six affected individuals from five unrelated families with two de novo and three maternally inherited pathogenic or likely pathogenic variants in THOC2 extending the genotypic and phenotypic spectrum. These comprise three rare missense THOC2 variants that affect evolutionarily conserved amino acid residues and reduce protein stability and two with canonical splice-site THOC2 variants that result in C-terminally truncated THOC2 proteins. We present detailed clinical assessment and functional studies on a de novo variant in a female with an epileptic encephalopathy and discuss an additional four families with rare variants in THOC2 with supportive evidence for pathogenicity. Severe neurocognitive features, including movement and seizure disorders, were observed in this cohort. Taken together our data show that even subtle alterations to the canonical molecular pathways such as mRNA export, otherwise essential for cellular life, can be compatible with life, but lead to NDDs in humans.

Somatic SLC35A2 variants in the brain are associated with intractable neocortical epilepsy. - Winawer, Melodie R; Griffin, Nicole G; Samanamud, Jorge; Baugh, Evan H; Rathakrishnan, Dinesh; Ramalingam, Senthilmurugan; Zagzag, David; Schevon, Catherine A; Dugan, Patricia; Hegde, Manu; Sheth, Sameer A; McKhann, Guy M; et al. (Ann Neurol, 2018)
OBJECTIVE: Somatic variants are a recognized cause of epilepsy-associated focal malformations of cortical development (MCD). We hypothesized that somatic variants may underlie a wider range of focal epilepsy, including nonlesional focal epilepsy (NLFE). Through genetic analysis of brain tissue, we evaluated the role of somatic variation in focal epilepsy with and without MCD. METHODS: We identified somatic variants through high-depth exome and ultra-high-depth candidate gene sequencing of DNA from epilepsy surgery specimens and leukocytes from 18 individuals with NLFE and 38 with focal MCD. RESULTS: We observed somatic variants in 5 cases in SLC35A2, a gene associated with glycosylation defects and rare X-linked epileptic encephalopathies. Nonsynonymous variants in SLC35A2 were detected in resected brain, and absent from leukocytes, in 3 of 18 individuals (17%) with NLFE, 1 female and 2 males, with variant allele frequencies (VAFs) in brain-derived DNA of 2 to 14%. Pathologic evaluation revealed focal cortical dysplasia type Ia (FCD1a) in 2 of the 3 NLFE cases. In the MCD cohort, nonsynonymous variants in SCL35A2 were detected in the brains of 2 males with intractable epilepsy, developmental delay, and magnetic resonance imaging suggesting FCD, with VAFs of 19 to 53%; Evidence for FCD was not observed in either brain tissue specimen. INTERPRETATION: We report somatic variants in SLC35A2 as an explanation for a substantial fraction of NLFE, a largely unexplained condition, as well as focal MCD, previously shown to result from somatic mutation but until now only in PI3K-AKT-mTOR pathway genes. Collectively, our findings suggest a larger role than previously recognized for glycosylation defects in the intractable epilepsies. Ann Neurol 2018.

STRetch: detecting and discovering pathogenic short tandem repeat expansions. - Dashnow, Harriet; Lek, Monkol; Phipson, Belinda; Halman, Andreas; Sadedin, Simon; Lonsdale, Andrew; Davis, Mark; Lamont, Phillipa; Clayton, Joshua S; Laing, Nigel G; MacArthur, Daniel G; Oshlack, Alicia (Genome Biol, 2018)
Short tandem repeat (STR) expansions have been identified as the causal DNA mutation in dozens of Mendelian diseases. Most existing tools for detecting STR variation with short reads do so within the read length and so are unable to detect the majority of pathogenic expansions. Here we present STRetch, a new genome-wide method to scan for STR expansions at all loci across the human genome. We demonstrate the use of STRetch for detecting STR expansions using short-read whole-genome sequencing data at known pathogenic loci as well as novel STR loci. STRetch is open source software, available from github.com/Oshlack/STRetch .
Keywords: Alleles; Chromosomes, Human; DNA Repeat Expansion; Genetic Loci; Genome, Human; Humans; Microsatellite Repeats; Polymerase Chain Reaction; Software

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.

The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

SLC13A5 is the second gene associated with Kohlschütter-Tönz syndrome. - Schossig, Anna; Bloch-Zupan, Agnès; Lussi, Adrian; Wolf, Nicole I; Raskin, Salmo; Cohen, Monika; Giuliano, Fabienne; Jurgens, Julie; Krabichler, Birgit; Koolen, David A; de Macena Sobreira, Nara Lygia; Maurer, Elisabeth; et al. (J Med Genet, 2017)
BACKGROUND: Kohlschütter-Tönz syndrome (KTZS) is a rare autosomal-recessive disease characterised by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI). It is frequently caused by biallelic mutations in ROGDI. Here, we report on individuals with ROGDI-negative KTZS carrying biallelic SLC13A5 mutations. METHODS: In the present cohort study, nine individuals from four families with the clinical diagnosis of KTZS and absence of ROGDI mutations as well as one patient with unexplained epileptic encephalopathy were investigated by clinical and dental evaluation, parametric linkage analysis (one family), and exome and/or Sanger sequencing. Dental histological investigations were performed on teeth from individuals with SLC13A5-associated and ROGDI-associated KTZS. RESULTS: Biallelic mutations in SLC13A5 were identified in 10 affected individuals. Epileptic encephalopathy usually presents in the neonatal and (less frequently) early infantile period. Yellowish to orange discolouration of both deciduous and permanent teeth, as well as wide interdental spaces and abnormal crown forms are major clinical signs of individuals with biallelic SLC13A5 mutations. Histological dental investigations confirmed the clinical diagnosis of hypoplastic AI. In comparison, the histological evaluation of a molar assessed from an individual with ROGDI-associated KTZS revealed hypocalcified AI. CONCLUSIONS: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.
Keywords: Alleles; Amelogenesis Imperfecta; Brain Diseases; Cohort Studies; Dementia; Epilepsy; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Mutation; Nuclear Proteins; Pedigree; Symporters; Tooth

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype

Survival beyond the perinatal period expands the phenotypes caused by mutations in GLE1. - Said, Edith; Chong, Jessica X; Hempel, Maja; Denecke, Jonas; Soler, Paul; Strom, Tim; Nickerson, Deborah A; Kubisch, Christian; Bamshad, Michael J; Lessel, Davor (Am J Med Genet A, 2017)
Mutations in GLE1 underlie Lethal Congenital Contracture syndrome (LCCS) and Lethal Arthrogryposis with Anterior Horn Cell Disease (LAAHD). Both LCCS and LAAHD are characterized by reduced fetal movements, congenital contractures, and a severe form of motor neuron disease that results in fetal death or death in the perinatal period, respectively. We identified bi-allelic mutations in GLE1 in two unrelated individuals with motor delays, feeding difficulties, and respiratory insufficiency who survived beyond the perinatal period. Each affected child had missense variants predicted to result in amino acid substitutions near the C-terminus of GLE1 that are predicted to disrupt protein-protein interaction or GLE1 protein targeting. We hypothesize that mutations that preserve function of the coiled-coil domain of GLE1 cause LAAHD whereas mutations that abolish the function of the coiled-coil domain cause LCCS. The phenotype of LAAHD is now expanded to include multiple individuals surviving into childhood suggesting that LAAHD is a misnomer and should be re-named Arthrogryposis with Anterior Horn Cell Disease (AAHD).
Keywords: Arthrogryposis; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Motor Disorders; Motor Neuron Disease; Mutation; Nucleocytoplasmic Transport Proteins; Pedigree; Pregnancy

SVachra: a tool to identify genomic structural variation in mate pair sequencing data containing inward and outward facing reads. - Hampton, Oliver A; English, Adam C; Wang, Mark; Salerno, William J; Liu, Yue; Muzny, Donna M; Han, Yi; Wheeler, David A; Worley, Kim C; Lupski, James R; Gibbs, Richard A (BMC Genomics, 2017)
BACKGROUND: Characterization of genomic structural variation (SV) is essential to expanding the research and clinical applications of genome sequencing. Reliance upon short DNA fragment paired end sequencing has yielded a wealth of single nucleotide variants and internal sequencing read insertions-deletions, at the cost of limited SV detection. Multi-kilobase DNA fragment mate pair sequencing has supplemented the void in SV detection, but introduced new analytic challenges requiring SV detection tools specifically designed for mate pair sequencing data. Here, we introduce SVachra - Structural Variation Assessment of CHRomosomal Aberrations, a breakpoint calling program that identifies large insertions-deletions, inversions, inter- and intra-chromosomal translocations utilizing both inward and outward facing read types generated by mate pair sequencing. RESULTS: We demonstrate SVachra's utility by executing the program on large-insert (Illumina Nextera) mate pair sequencing data from the personal genome of a single subject (HS1011). An additional data set of long-read (Pacific BioSciences RSII) was also generated to validate SV calls from SVachra and other comparison SV calling programs. SVachra exhibited the highest validation rate and reported the widest distribution of SV types and size ranges when compared to other SV callers. CONCLUSIONS: SVachra is a highly specific breakpoint calling program that exhibits a more unbiased SV detection methodology than other callers.
Keywords: Genetic Variation; Genomics; Sequence Analysis, DNA

Somatic mosaicism for a lethal TRPV4 mutation results in non-lethal metatropic dysplasia. - Weinstein, Michael M; Kang, Taekyu; Lachman, Ralph S; Bamshad, Michael; Nickerson, Deborah A; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2016)
Dominant mutations in TRPV4, which encodes the Transient Receptor Potential Cation Channel Subfamily V Member 4 calcium channel, result in a series of musculoskeletal disorders that include a set of peripheral neuropathies and a broad phenotypic spectrum of skeletal dysplasias. The skeletal phenotypes range from brachyolmia, in which there is scoliosis with mild short stature, through perinatal lethal metatropic dysplasia. We describe a case with phenotypic findings consistent with metatropic dysplasia, but in whom no TRPV4 mutation was detected by Sanger sequence analysis. Exome sequence analysis identified a known lethal metatropic dysplasia mutation, TRPV4 , which was present at lower frequency than would be expected for a heterozygous change. The affected individual was shown to be a somatic mosaic for the mutation, providing an explanation for the milder than expected phenotype. The data illustrate that high-throughput sequencing of genomic DNA can facilitate detection of mosaicism with higher sensitivity than Sanger sequence analysis and identify a new genetic mechanism for metatropic dysplasia. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; DNA Mutational Analysis; Dwarfism; Exons; Genetic Association Studies; Humans; Infant; Magnetic Resonance Imaging; Mosaicism; Mutation; Osteochondrodysplasias; Phenotype; Physical Examination; Radiography; TRPV Cation Channels

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Yuan, Bo; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

A Syndromic Intellectual Disability Disorder Caused by Variants in TELO2, a Gene Encoding a Component of the TTT Complex. - You, Jing; Sobreira, Nara L; Gable, Dustin L; Jurgens, Julie; Grange, Dorothy K; Belnap, Newell; Siniard, Ashley; Szelinger, Szabolcs; Schrauwen, Isabelle; Richholt, Ryan F; Vallee, Stephanie E; Dinulos, Mary Beth P; et al. (Am J Hum Genet, 2016)
The proteins encoded by TELO2, TTI1, and TTI2 interact to form the TTT complex, a co-chaperone for maturation of the phosphatidylinositol 3-kinase-related protein kinases (PIKKs). Here we report six affected individuals from four families with intellectual disability (ID) and neurological and other congenital abnormalities associated with compound heterozygous variants in TELO2. Although their fibroblasts showed reduced steady-state levels of TELO2 and the other components of the TTT complex, PIKK functions were normal in cellular assays. Our results suggest that these TELO2 missense variants result in loss of function, perturb TTT complex stability, and cause an autosomal-recessive syndromic form of ID.
Keywords: Adolescent; Carrier Proteins; Child; Female; Humans; Intellectual Disability; Male; Molecular Chaperones; Pedigree; Phosphatidylinositol 3-Kinases; Protein-Serine-Threonine Kinases; Telomere-Binding Proteins

Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT). - Scholl, Hendrik P N; Moore, Anthony T; Koenekoop, Robert K; Wen, Yuquan; Fishman, Gerald A; van den Born, L Ingeborgh; Bittner, Ava; Bowles, Kristen; Fletcher, Emily C; Collison, Frederick T; Dagnelie, Gislin; Degli Eposti, Simona; et al. (PLoS One, 2015)
UNLABELLED: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eight of 18 patients (44%) showed a ≥20% increase and 4 of 18 (22%) showed a ≥40% increase in functional retinal area determined from Goldmann visual fields; 12 (67%) and 5 (28%) of 18 patients showed a ≥5 and ≥10 ETDRS letter score increase of visual acuity, respectively, in one or both eyes at two or more visits within 2 months of treatment. In two patients who underwent fMRI, a significant positive response was measured to stimuli of medium contrast, moving, pattern targets in both left and right hemispheres of the occipital cortex. There were no serious adverse events. Treatment-related adverse events were transient and the most common included headache, photophobia, nausea, vomiting, and minor biochemical abnormalities. Measuring the outer segment length of the photoreceptor layer with high-definition optical coherence tomography was highly predictive of treatment responses with responders having a significantly larger baseline outer segment thickness (11.7 ± 4.8 μm, mean ± 95% CI) than non-responders (3.5 ± 1.2 μm). This structure-function relationship suggests that treatment with QLT091001 is more likely to be efficacious if there is sufficient photoreceptor integrity. TRIAL REGISTRATION: ClinicalTrials.gov NCT01014052.
Keywords: Acyltransferases; Administration, Oral; Adult; Anticarcinogenic Agents; Cerebral Cortex; Child; cis-trans-Isomerases; Drug Dosage Calculations; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Radiography; Retinal Ganglion Cells; Retinal Neurons; Retinitis Pigmentosa; Treatment Outcome; Visual Acuity; Visual Fields; Vitamin A; Young Adult

A second locus for Schneckenbecken dysplasia identified by a mutation in the gene encoding inositol polyphosphate phosphatase-like 1 (INPPL1). - Lee, Hane; Nevarez, Lisette; Lachman, Ralph S; Wilcox, William R; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2015)
Keywords: Exome; Gene Expression; Genetic Loci; Gestational Age; Homozygote; Humans; Hydrops Fetalis; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Stillbirth

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic mosaicism: implications for disease and transmission genetics. - Campbell, Ian M; Shaw, Chad A; Stankiewicz, Pawel; Lupski, James R (Trends Genet, 2015)
Nearly all of the genetic material among cells within an organism is identical. However, single-nucleotide variants (SNVs), small insertions/deletions (indels), copy-number variants (CNVs), and other structural variants (SVs) continually accumulate as cells divide during development. This process results in an organism composed of countless cells, each with its own unique personal genome. Thus, every human is undoubtedly mosaic. Mosaic mutations can go unnoticed, underlie genetic disease or normal human variation, and may be transmitted to the next generation as constitutional variants. We review the influence of the developmental timing of mutations, the mechanisms by which they arise, methods for detecting mosaic variants, and the risk of passing these mutations on to the next generation.
Keywords: Animals; Genetic Diseases, Inborn; Genome, Human; Humans; Mosaicism; Mutagenesis, Insertional; Mutation; Polymorphism, Single Nucleotide; Risk; Trinucleotide Repeat Expansion

Somatic p.T771R KDR (VEGFR2) Mutation Arising in a Sporadic Angioma During Ramucirumab Therapy. - Lim, Young H; Odell, Ian D; Ko, Christine J; Choate, Keith A (JAMA Dermatol, 2015)
IMPORTANCE: Inhibition of angiogenesis is an effective anticancer strategy because neoplasms require a rich blood supply. Ramucirumab, approved by the US Food and Drug Administration in 2014 to treat gastric adenocarcinomas and non-small cell lung carcinomas, targets vascular endothelial growth factor 2 (VEGFR2). We identified a patient prescribed a regimen of irinotecan hydrochloride, cetuximab, and ramucirumab for metastatic rectal cancer (diagnosed in November 2013 and treated through early January 2015) who developed a new-onset, expanding vascular lesion on his right leg. Via exome sequencing, we found that the lesion contained a single somatic mutation in KDR (encodes VEGFR2), possibly in response to ramucirumab. Vascular tumors are not a known complication of antiangiogenic therapeutics. OBSERVATIONS: Exome sequencing of the well-demarcated, blanching vascular lesion on the lateral right shin revealed a somatic p.T771R mutation in KDR, without evidence of other somatic mutations or loss of heterozygosity. Histological features included lobules of small vessels within the dermis, resembling a tufted angioma. CONCLUSIONS AND RELEVANCE: A potential adverse effect of ramucirumab in combination therapy is the development of sporadic angiomas. The p.T771R mutation was previously implicated in autophosphorylation of VEGFR2 and reported in angiosarcomas alongside other driver mutations. Our observations suggest that this mutation confers a proliferative advantage in the setting of ramucirumab therapy. Patients receiving ramucirumab should be monitored for the development of new vascular lesions.
Keywords: Adult; Angiogenesis Inhibitors; Antibodies, Monoclonal; Antineoplastic Combined Chemotherapy Protocols; Camptothecin; Cetuximab; Hemangioma; Humans; Irinotecan; Male; Mutation; Rectal Neoplasms; Skin Neoplasms; Vascular Endothelial Growth Factor Receptor-2

Somatic V600E BRAF Mutation in Linear and Sporadic Syringocystadenoma Papilliferum. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; Bilguvar, Kaya; McNiff, Jennifer M; Choate, Keith A (J Invest Dermatol, 2015)
Keywords: Biopsy, Needle; Child; Cystadenoma; Female; Gene Expression Regulation, Neoplastic; Humans; Immunohistochemistry; Mutation; Proto-Oncogene Proteins B-raf; Sweat Gland Neoplasms; Syringoma

Structural variation mutagenesis of the human genome: Impact on disease and evolution. - Lupski, James R (Environ Mol Mutagen, 2015)
Watson-Crick base-pair changes, or single-nucleotide variants (SNV), have long been known as a source of mutations. However, the extent to which DNA structural variation, including duplication and deletion copy number variants (CNV) and copy number neutral inversions and translocations, contribute to human genome variation and disease has been appreciated only recently. Moreover, the potential complexity of structural variants (SV) was not envisioned; thus, the frequency of complex genomic rearrangements and how such events form remained a mystery. The concept of genomic disorders, diseases due to genomic rearrangements and not sequence-based changes for which genomic architecture incite genomic instability, delineated a new category of conditions distinct from chromosomal syndromes and single-gene Mendelian diseases. Nevertheless, it is the mechanistic understanding of CNV/SV formation that has promoted further understanding of human biology and disease and provided insights into human genome and gene evolution. Environ. Mol. Mutagen. 56:419-436, 2015. © 2015 Wiley Periodicals, Inc.
Keywords: Animals; Evolution, Molecular; Gene Dosage; Genetic Predisposition to Disease; Genome, Human; Genomic Structural Variation; Humans; Mutagenesis

Successful diagnosis of HIBCH deficiency from exome sequencing and positive retrospective analysis of newborn screening cards in two siblings presenting with Leigh's disease. - Stiles, Ashlee R; Ferdinandusse, Sacha; Besse, Arnaud; Appadurai, Vivek; Leydiker, Karen B; Cambray-Forker, E J; Bonnen, Penelope E; Abdenur, Jose E (Mol Genet Metab, 2015)
PURPOSE: 3-Hydroxyisobutryl-CoA hydrolase (HIBCH) deficiency is a rare disorder of valine metabolism. We present a family with the oldest reported subjects with HIBCH deficiency and provide support that HIBCH deficiency should be included in the differential for elevated hydroxy-C4-carnitine in newborn screening (NBS). METHODS: Whole exome sequencing (WES) was performed on one affected sibling. HIBCH enzymatic activity was measured in patient fibroblasts. Acylcarnitines were measured by electrospray ionization tandem mass spectrometry (ESI-MS/MS). Disease incidence was estimated using a cohort of 61,434 individuals. RESULTS: Two siblings presented with infantile-onset, progressive neurodegenerative disease. WES identified a novel homozygous variant in HIBCH c.196C>T; p.Arg66Trp. HIBCH enzymatic activity was significantly reduced in patients' fibroblasts. Acylcarnitine analysis showed elevated hydroxy-C4-carnitine in blood spots of both affected siblings, including in their NBS cards, while plasma acylcarnitines were normal. Estimates show HIBCH deficiency incidence as high as 1 in ~130,000 individuals. CONCLUSION: We describe a novel family with HIBCH deficiency at the biochemical, enzymatic and molecular level. Disease incidence estimates indicate HIBCH deficiency may be under-diagnosed. This together with the elevated hydroxy-C4-carnitine found in the retrospective analysis of our patient's NBS cards suggests that this disorder could be screened for by NBS programs and should be added to the differential diagnosis for elevated hydroxy-C4-carnitine which is already measured in most NBS programs using MS/MS.
Keywords: Abnormalities, Multiple; Adolescent; Amino Acid Metabolism, Inborn Errors; Carnitine; Child; Child, Preschool; Cohort Studies; Exome; Female; Fibroblasts; Humans; Infant; Infant, Newborn; Leigh Disease; Male; Mass Spectrometry; Neonatal Screening; Prognosis; Retrospective Studies; Sequence Analysis, DNA; Siblings; Thiolester Hydrolases

Sclerocornea in a patient with van den Ende-Gupta syndrome homozygous for a SCARF2 microdeletion. - Migliavacca, Michele P; Sobreira, Nara L M; Antonialli, Graziela P M; Oliveira, Mariana M; Melaragno, Maria Isabel S A; Casteels, Ingele; de Ravel, Thomy; Brunoni, Decio; Valle, David; Perez, Ana Beatriz A (Am J Med Genet A, 2014)
Van den Ende-Gupta Syndrome (VDEGS) is an autosomal recessive disorder characterized by blepharophimosis, distinctive nose, hypoplastic maxilla, and skeletal abnormalities. Using homozygosity mapping in four VDEGS patients from three consanguineous families, Anastacio et al. [Anastacio et al. (2010); Am J Hum Genet 87:553-559] identified homozygous mutations in SCARF2, located at 22q11.2. Bedeschi et al. [2010] described a VDEGS patient with sclerocornea and cataracts with compound heterozygosity for the common 22q11.2 microdeletion and a hemizygous SCARF2 mutation. Because sclerocornea had been described in DiGeorge-velo-cardio-facial syndrome but not in VDEGS, they suggested that the ocular abnormalities were caused by the 22q11.2 microdeletion. We report on a 23-year-old male who presented with bilateral sclerocornea and the VDGEGS phenotype who was subsequently found to be homozygous for a 17 bp deletion in exon 4 of SCARF2. The occurrence of bilateral sclerocornea in our patient together with that of Bedeschi et al., suggests that the full VDEGS phenotype may include sclerocornea resulting from homozygosity or compound heterozygosity for loss of function variants in SCARF2.
Keywords: Abnormalities, Multiple; Adult; Arachnodactyly; Blepharophimosis; Bone and Bones; Chromosomes, Human, Pair 22; Contracture; Cornea; Corneal Diseases; Exons; Facies; Hand Deformities, Congenital; Homozygote; Humans; Male; Phenotype; Radiography; Scavenger Receptors, Class F; Sequence Analysis, DNA; Sequence Deletion; Young Adult

Solving glycosylation disorders: fundamental approaches reveal complicated pathways. - Freeze, Hudson H; Chong, Jessica X; Bamshad, Michael J; Ng, Bobby G (Am J Hum Genet, 2014)
Over 100 human genetic disorders result from mutations in glycosylation-related genes. In 2013, a new glycosylation disorder was reported every 17 days. This trend will probably continue given that at least 2% of the human genome encodes glycan-biosynthesis and -recognition proteins. Established biosynthetic pathways provide many candidate genes, but finding unanticipated mutated genes will offer new insights into glycosylation. Simple glycobiomarkers can be used in narrowing the candidates identified by exome and genome sequencing, and those can be validated by glycosylation analysis of serum or cells from affected individuals. Model organisms will expand the understanding of these mutations' impact on glycosylation and pathology. Here, we highlight some recently discovered glycosylation disorders and the barriers, breakthroughs, and surprises they presented. We predict that some glycosylation disorders might occur with greater frequency than current estimates of their prevalence. Moreover, the prevalence of some disorders differs substantially between European and African Americans.
Keywords: Congenital Disorders of Glycosylation; Exome; Genome, Human; Glucose; Glycogen; Glycosylation; Homeostasis; Humans; Mannose; Mutation

Somatic HRAS p.G12S mutation causes woolly hair and epidermal nevi. - Levinsohn, Jonathan L; Teng, Joyce; Craiglow, Brittany G; Loring, Erin C; Burrow, T Andrew; Mane, Shrikant S; Overton, John D; Lifton, Richard P; McNiff, Jennifer M; Lucky, Anne W; Choate, Keith A (J Invest Dermatol, 2014)
Keywords: Adherens Junctions; Child; Exome; Female; Genes, ras; Hair; Hair Diseases; Hair Follicle; Humans; Intermediate Filaments; Mosaicism; Mutation; Nevus; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction

Somatic mutations in cerebral cortical malformations. - Morita, Hiroyuki; Komuro, Issei (N Engl J Med, 2014)
Keywords: Cerebral Cortex; DNA Mutational Analysis; Humans; Malformations of Cortical Development; Mutation

Somatic mutations in cerebral cortical malformations. - Jamuar, Saumya S; Lam, Anh-Thu N; Kircher, Martin; D'Gama, Alissa M; Wang, Jian; Barry, Brenda J; Zhang, Xiaochang; Hill, Robert Sean; Partlow, Jennifer N; Rozzo, Aldo; Servattalab, Sarah; Mehta, Bhaven K; et al. (N Engl J Med, 2014)
BACKGROUND: Although there is increasing recognition of the role of somatic mutations in genetic disorders, the prevalence of somatic mutations in neurodevelopmental disease and the optimal techniques to detect somatic mosaicism have not been systematically evaluated. METHODS: Using a customized panel of known and candidate genes associated with brain malformations, we applied targeted high-coverage sequencing (depth, ≥200×) to leukocyte-derived DNA samples from 158 persons with brain malformations, including the double-cortex syndrome (subcortical band heterotopia, 30 persons), polymicrogyria with megalencephaly (20), periventricular nodular heterotopia (61), and pachygyria (47). We validated candidate mutations with the use of Sanger sequencing and, for variants present at unequal read depths, subcloning followed by colony sequencing. RESULTS: Validated, causal mutations were found in 27 persons (17%; range, 10 to 30% for each phenotype). Mutations were somatic in 8 of the 27 (30%), predominantly in persons with the double-cortex syndrome (in whom we found mutations in DCX and LIS1), persons with periventricular nodular heterotopia (FLNA), and persons with pachygyria (TUBB2B). Of the somatic mutations we detected, 5 (63%) were undetectable with the use of traditional Sanger sequencing but were validated through subcloning and subsequent sequencing of the subcloned DNA. We found potentially causal mutations in the candidate genes DYNC1H1, KIF5C, and other kinesin genes in persons with pachygyria. CONCLUSIONS: Targeted sequencing was found to be useful for detecting somatic mutations in patients with brain malformations. High-coverage sequencing panels provide an important complement to whole-exome and whole-genome sequencing in the evaluation of somatic mutations in neuropsychiatric disease. (Funded by the National Institute of Neurological Disorders and Stroke and others.).
Keywords: Cerebral Cortex; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Humans; Lissencephaly; Magnetic Resonance Imaging; Malformations of Cortical Development; Mutation; Periventricular Nodular Heterotopia

Structural variation and missense mutation in SBDS associated with Shwachman-Diamond syndrome. - Carvalho, Claudia M B; Zuccherato, Luciana W; Williams, Christopher L; Neill, Nicholas J; Murdock, David R; Bainbridge, Matthew; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Ip, Wan; Guillerman, Robert Paul; Lupski, James R; et al. (BMC Med Genet, 2014)
BACKGROUND: Shwachman-Diamond syndrome (SDS) is an autosomal recessive ribosomopathy caused mainly by compound heterozygous mutations in SBDS. Structural variation (SV) involving the SBDS locus has been rarely reported in association with the disease. We aimed to determine whether an SV contributed to the pathogenesis of a case lacking biallelic SBDS point mutations. CASE PRESENTATION: Whole exome sequencing was performed in a patient with SDS lacking biallelic SBDS point mutations. Array comparative genomic hybridization and Southern blotting were used to seek SVs across the SBDS locus. Locus-specific polymerase chain reaction (PCR) encompassing flanking intronic sequence was also performed to investigate mutation within the locus. RNA expression and Western blotting were performed to analyze allele and protein expression. We found the child harbored a single missense mutation in SBDS (c.98A > C; p.K33T), inherited from the mother, and an SV in the SBDS locus, inherited from the father. The missense allele and SV segregated in accordance with Mendelian expectations for autosomal recessive SDS. Complementary DNA and western blotting analysis and locus specific PCR support the contention that the SV perturbed SBDS protein expression in the father and child. CONCLUSION: Our findings implicate genomic rearrangements in the pathogenesis of some cases of SDS and support patients lacking biallelic SBDS point mutations be tested for SV within the SBDS locus.
Keywords: Abdomen; Alleles; Bone Marrow Diseases; Cell Line, Transformed; Child, Preschool; Comparative Genomic Hybridization; DNA Mutational Analysis; Exocrine Pancreatic Insufficiency; Female; Gene Order; Humans; Lipomatosis; Mutagenesis, Insertional; Mutation; Mutation, Missense; Pedigree; Proteins; Radiography, Abdominal; Ultrasonography

Somatic and germline CACNA1D calcium channel mutations in aldosterone-producing adenomas and primary aldosteronism. - Scholl, Ute I; Goh, Gerald; Stölting, Gabriel; de Oliveira, Regina Campos; Choi, Murim; Overton, John D; Fonseca, Annabelle L; Korah, Reju; Starker, Lee F; Kunstman, John W; Prasad, Manju L; Hartung, Erum A; et al. (Nat Genet, 2013)
Adrenal aldosterone-producing adenomas (APAs) constitutively produce the salt-retaining hormone aldosterone and are a common cause of severe hypertension. Recurrent mutations in the potassium channel gene KCNJ5 that result in cell depolarization and Ca(2+) influx cause ∼40% of these tumors. We identified 5 somatic mutations (4 altering Gly403 and 1 altering Ile770) in CACNA1D, encoding a voltage-gated calcium channel, among 43 APAs without mutated KCNJ5. The altered residues lie in the S6 segments that line the channel pore. Both alterations result in channel activation at less depolarized potentials; Gly403 alterations also impair channel inactivation. These effects are inferred to cause increased Ca(2+) influx, which is a sufficient stimulus for aldosterone production and cell proliferation in adrenal glomerulosa. We also identified de novo germline mutations at identical positions in two children with a previously undescribed syndrome featuring primary aldosteronism and neuromuscular abnormalities. These findings implicate gain-of-function Ca(2+) channel mutations in APAs and primary aldosteronism.
Keywords: Adrenal Cortex Neoplasms; Adrenocortical Adenoma; Aldosterone; Amino Acid Sequence; Calcium Channels, L-Type; Cell Line; Child; Child, Preschool; Female; Germ-Line Mutation; Humans; Hyperaldosteronism; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Sequence Alignment

SEQCHIP: a powerful method to integrate sequence and genotype data for the detection of rare variant associations. - Liu, Dajiang J; Leal, Suzanne M (Bioinformatics, 2012)
MOTIVATION: Next-generation sequencing greatly increases the capacity to detect rare-variant complex-trait associations. However, it is still expensive to sequence a large number of samples and therefore often small datasets are used. Given cost constraints, a potentially more powerful two-step strategy is to sequence a subset of the sample to discover variants, and genotype the identified variants in the remaining sample. If only cases are sequenced, directly combining sequence and genotype data will lead to inflated type-I errors in rare-variant association analysis. Although several methods have been developed to correct for the bias, they are either underpowered or theoretically invalid. We proposed a new method SEQCHIP to integrate genotype and sequence data, which can be used with most existing rare-variant tests. RESULTS: It is demonstrated using both simulated and real datasets that the SEQCHIP method has controlled type-I errors, and is substantially more powerful than all other currently available methods. AVAILABILITY: SEQCHIP is implemented in an R-Package and is available at http://linkage.rockefeller.edu/suzanne/seqchip/Seqchip.html.
Keywords: Adenoma; Case-Control Studies; Colorectal Neoplasms; Genetic Association Studies; Genetic Variation; Genotype; Humans; Phenotype; Sequence Analysis, DNA; Software

SimRare: a program to generate and analyze sequence-based data for association studies of quantitative and qualitative traits. - Li, Biao; Wang, Gao; Leal, Suzanne M (Bioinformatics, 2012)
MOTIVATION: Currently, there is great interest in detecting complex trait rare variant associations using next-generation sequence data. On a monthly basis, new rare variant association methods are published. It is difficult to evaluate these methods because there is no standard to generate data and often comparisons are biased. In order to fairly compare rare variant association methods, it is necessary to generate data using realistic population demographic and phenotypic models. RESULT: SimRare is an interactive program that integrates generation of rare variant genotype/phenotype data and evaluation of association methods using a unified platform. Variant data are generated for gene regions using forward-time simulation that incorporates realistic population demographic and evolutionary scenarios. Phenotype data can be obtained for both case-control and quantitative traits. SimRare has a user-friendly interface that allows for easy entry of genetic and phenotypic parameters. Novel rare variant association methods implemented in R can also be imported into SimRare, to evaluate their performance and compare results, e.g. power and Type I error, with other currently available methods both numerically and graphically.
Keywords: Genetic Association Studies; Genetic Variation; Humans; Phenotype; Quantitative Trait, Heritable; Software